1945
DOI: 10.6028/jres.035.024
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of solid and liquid ethylbenzene from 0 to 300 degrees K

Abstract: The following properties of a sample of high purity ethylbenzene were measured: (1) Specific heat of solid and liquid from 15 0 to 300 0 Ie; (2) triple-point temperature (-95.005 ±0.01O° C for pure ethyl benzene) ; (3) heat of fusion (86.47 into i g -1); (4) heat of vaporization at 294 0 Ie (400.15 into j g -1); and (5) vapor pressure from 273 0 to 296 0 Ie. With these experimental data, the enthalpy and entropy of the solid and of the liquid in the range 0 0 to 300 0 Ie were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1947
1947
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…13 The agreement in the heat capacities was satisfactory above 60 o K, while the heats of fusion differed by 0.19 percent. The actual heat capacity values used in constructing this plot can all be found elsewhere.…”
mentioning
confidence: 83%
“…13 The agreement in the heat capacities was satisfactory above 60 o K, while the heats of fusion differed by 0.19 percent. The actual heat capacity values used in constructing this plot can all be found elsewhere.…”
mentioning
confidence: 83%
“…4.1E+1 3.2E+3 Osborn and Douslin, 1974 Willingham el al., 1945Osborn and Douslin, 1974Willingham et al, 1945 Oshorn and Douslin, 1974Osborn and Douslin, 1974Scott and Brickwedde, 1945 Oshorn and Scott, 1980 Chirico el al., IY89a Chirico el al., 1989aSteele et al, 1988 Steele ef al., 1988Steele et al, 1988Steele et al, 1988Biddiscombe and Martin, 1958 Biddiscomhe and Martin, 1958Biddiscombe and Martin, 1958Biddiscombe and Martin, 1958Biddiscombe and Martin, 1958 Biddsiconihc and Martin, 19% Biddiscomhe and Martin, 1958Biddiscombe and Martin, 1958de Kruif et al 1983 Dreishach and Shrader, 1949 Chirico el al., 1990Chirico et al, 1990 Oshorn and Douslin, 1966Osborn and Douslin, 1966 Osborn and Douslin, I966 Oshorn and Douslin, 1966Forziati et al, 1950 Forziati el al., 1950Forziati et al. 1950 Oshorn and Douslin, 1974 Oshorn and Scott, 1980Scott et al, 1962Messerly et al, 1975 Meycr and Hotz, 1973 Oshorn and Douslin, 1968 Oshorn and Douslin.…”
mentioning
confidence: 99%
“…Saturation heat capacities calculated with the equation of state are compared in Fig. 25; the equation deviates from the data of Scott and Brickwedde, 125 Paramo et al, 95 and Chirico et al 29 by up to 0.4%. The data of Blacet et al, 152 Huff-man et al, 80 and Smith and Andrews 153 show substantially higher deviations.…”
Section: -19 Equations Of State For the Xylene Isomersmentioning
confidence: 73%
“…of the vapor pressure generally within 0.8% (with the highest deviations in the data of Akhundov et al 134 ). The data reported by Scott and Brickwedde, 125 Rodrigues et al, 1 Aucejo et al, 46 Buck et al, 126 and Chianese and Marrelli 102 are all in good agreement, and the equation of state shows deviations of up to 0.1%. The data reported by Akhundov, 132 Zhao and Kabadi, 136 and Willingham et al 40 deviate from the data reported by Ambrose 20 and Ambrose et al 16 by about 0.4%-0.6%.…”
Section: -19 Equations Of State For the Xylene Isomersmentioning
confidence: 80%